Tingkat Pemahaman Produk, Difirensiasi, Dan Kualitas Sumberdaya Manusia Atas Keputusan Nasabah Perbankan Syariah - Rachmad Nor Firman; Novi Dian Pertiwi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2021)
The growing growth of the banking industry creates increasingly fierce competition between the Islamic banking industry, so that it will make consumers have many alternative choices before deciding which bank to go to to conduct Islamic banking transactions. This study aims to reveal the level of understanding of the quality of customer human resources on customer decisions, perceptions of product differentiation on customer decisions. This study uses qualitative research, data collected by means of interviews (interviews), observation, documentation and then analyzed by descriptive analysis method. The research results prove that customer perceptions of product differentiation, level of product understanding, and quality of human resources have a positive influence on customer decisions in Islamic banking. use the services of Islamic banking.